Prinsip Pelelangan Obyek Hak Tanggungan secara Parate Executie akibat Wanprestasi dalam Perjanjian Kredit - Rumawi Rumawi (Fakultas Hukum Universitas Islam Jember, 2014)
Hak tanggungan (mortgage) is right for the land to guarantee repayment of certain debt, which is given precedence to krediror certain position against other creditors. That is, if the debtor default, the creditor first Mortgage holder takes precedence over other creditors and given the right to do the sales object security rights through public auction in accordance legislation. Transparency in Tender Object Mortgage. Transparency is done with the announcement of the auction object mortgage, mortgage before the object and the announcement of the winner of the auction is done openly in front of the auction bidders. The auction is parate objects mortgage executie can sell ourselves seller if no bidders interested in buying a mortgage auction object.